PENGARUH PEMERIKSAAN PAJAK, JUMLAH PENGUSAHA KENA PAJAK DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI - Amanah, Nurul; Suhendar, Dadang; Indrawan, Rizki (Jurnal Riset Keuangan dan Akuntansi, 2024)
This study aims to analyze the effect of tax audits, the number of taxable entrepreneurs and tax collection on value-added tax revenue, case studies at KPP Pratama Kuningan and KPP Pratama Cirebon Satu. The population in this study is tax audit data, the number of taxable entrepreneurs, tax collection and value-added tax revenue at KPP Pratama Kuningan and KPP Pratama Cirebon Satu 2018-2022 per month totaling 60 months at each KPP. The sampling used in this study used a saturated sample where all populations were used as samples. This study used multiple linear regression method. Statistical testing using SPSS Version 23. The results showed that the results of simultaneous tests of Tax Audit, Number of Taxable Entrepreneurs and Tax Collection had a significant effect on Value Added Tax Revenue. As for the partial test results of the Tax Audit variables, the Number of Taxable Entrepreneurs and Tax Collection have a positive and significant effect on Value Added Tax Revenue. Keywords : Tax Audit, Number of Taxable Entrepreneurs, Tax Collection, Value Added Tax Revenue.